2013
DOI: 10.4047/jap.2013.5.3.256
|View full text |Cite
|
Sign up to set email alerts
|

Computerized analysis of occlusal contacts in bruxism patients treated with occlusal splint therapy

Abstract: PURPOSEOcclusal splints are commonly used to prevent tooth wear caused by bruxism. However, the effects of splints on occlusion are still unclear. Although it is rarely alluded in literature, splints can provoke severe occlusal alterations and other complications. This study was aimed to identify differences in the responses of individuals with bruxism and healthy individuals to a full-arch maxillary stabilization splint in terms of occlusal changes.MATERIALS AND METHODSOcclusal contacts in 20 (5 male, 15 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
0
19
1
2
Order By: Relevance
“…Although it could be hypothesized this finding to be related with the dental abrasion, typical of subjects affected by bruxism, it seems particularly interesting to compare this result with the findings of Gumus et al . 25 that, as a secondary outcome of their study, similarly compared the OT of subjects affected by bruxism with a healthy group, without finding any statistically significant difference. Gumus et al .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although it could be hypothesized this finding to be related with the dental abrasion, typical of subjects affected by bruxism, it seems particularly interesting to compare this result with the findings of Gumus et al . 25 that, as a secondary outcome of their study, similarly compared the OT of subjects affected by bruxism with a healthy group, without finding any statistically significant difference. Gumus et al .…”
Section: Discussionmentioning
confidence: 96%
“…24 demonstrated that subjects affected by temporomandibular disorders (TMD) have longer OT compared with healthy subjects suggesting that the presence of TMD is associated with a lower occlusal stability, while another study by Gumus et al . 25 investigated the effect of an occlusal splint treatment in subjects affected by bruxism on the occlusion time and other T-Scan parameters and observed the absence of influence of bruxism on the occlusion time.…”
Section: Introductionmentioning
confidence: 99%
“…Occlusion time (OT) is the time from the first contact of occluding teeth to maximum intercuspation, and disocclusion time (DT) is the time from maximum intercuspation to complete disocclusion during lateral movement. (17)(18)(19) The clinical goal is to reach maximum intercuspation in less than 0.2 second and disocclude all posterior teeth in less than 0.4 second. (20) The shorter the OT, the less time required to contact all teeth and the fewer the prematurities as the patient closes into maximum intercuspation, indicating occlusal contact simultaneity and equilibration.…”
Section: Introductionmentioning
confidence: 99%
“…(retração e inflamação), a mucosa (marcas dos dentes na língua e bochecha), aos músculos (sensibilidade dolorosa, fadiga e hipertrofia) e ainda, cefaleia, ruídos audíveis de apertar e ranger dos dentes e os desenvolvidos pela articulação temporomandibular (ODEBRECHT; BORTOLON, 2004;MANZINI;KATO, 2005; AVIDAN et al, 2009;LOBBEZOO, 2009;DE LUCA CANTO et al, 2013;GÜMÜS et al, 2013; DE LUCA SUMIYA et al, 2014 O sono REM é mais profundo e representa cerca de 25% do período total de sono. Neste processo ocorre o aumento do fluxo sanguíneo, frequência cardíaca, atividade respiratória, temperatura corporal e pressão sanguínea, associado aos movimentos rápidos dos olhos (COLOMBO, 2002; KATO et al, 2011).…”
Section: Introductionunclassified
“…Os sinais e sintomas clínicos mais comuns evidenciados nos bruxômanos por profissionais da área de saúde estão relacionados aos dentes (hipersensibilidade, desgaste, mobilidade, anquilose, fraturas recorrentes de restaurações e reabsorção radicular), a gengiva (retração e inflamação), a mucosa (marcas dos dentes na língua e bochecha), aos músculos (sensibilidade dolorosa, fadiga e hipertrofia) e ainda, cefaleia, ruídos audíveis de apertar e ranger dos dentes e os desenvolvidos pela articulação temporomandibular (ODEBRECHT; BORTOLON, 2004;MANZINI;KATO, 2005;AVIDAN et al, 2009;LOBBEZOO, 2009;DE LUCA CANTO et al, 2013;GÜMÜS et al, 2013;DE LUCA SUMIYA et al, 2014).…”
Section: Introductionunclassified